The Hand Puppet Book: The Multicultural-Based Media Developed as Literacy Materials for 4th Grade Students - Atika Susanti; Ady Darmansyah; Pratiwi Pujiastuti (Universitas Negeri Padang, 2023)
The objective of this research study is to develop a multicultural-based Hand Puppet Book media that is appropriate as literacy material for fourth-grade students. This research follows the Research and Development methodology. The development process adopts seven out of the ten steps formulated by Borg & Gall, which include:1) preliminary study, 2) planning, 3) developing a preliminary form of product, 4) preliminary field testing, 5) main product revision, 6) main field testing, and 7) operational product revisions. The subjects in this study were 4th-grade elementary school students in Depok District. During the initial study, data collection was conducted through various methods including observation, interviews, and questionnaires. The validation process involved material experts, media experts, and gathering feedback from both teachers and students. The outcome of the research is the development of a Hand Puppet Book media that incorporates multicultural content and promotes tolerance values. The media has been deemed suitable for implementation based on the validation results from material and media experts, as well as the trials conducted in schools, which categorized it as